1999
DOI: 10.1161/01.hyp.34.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Transcapillary Albumin Leakage in Essential Hypertension

Abstract: Abstract-Microalbuminuria (an increased urinary albumin excretion that is not detectable by the usual dipstick methods for macroproteinuria) predicts cardiovascular events in essential hypertensive patients. A possible reason for this behavior is that albumin leaks through exaggeratedly permeant glomeruli exposed to the damaging impact of subclinical atherogenesis. To evaluate this possibility, the transcapillary escape rate of albumin (TER alb , the 1-hour decline rate of intravenous 125 I-albumin), a paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 41 publications
2
38
1
7
Order By: Relevance
“…However, we did not find any difference in endothelial permeability between these groups. It seems that elevated blood pressure and disruption of the starling equilibrium could increase endothelial permeability (Parving and Gyntelberg 1973); however, in this study, preservation of endothelial permeability in 2K1C hypertensive group indicated that change of hemodynamic forces in hypertension does not contribute in endothelial permeability (Pedrinelli et al 1999). In agreement to our results, a recent clinical study evaluated systemic capillary permeability using TERalb (another parameter for estimation of capillary permeability) and found that systemic capillary permeability was not different between normotensive and hypertensive group (Dell'Omo et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…However, we did not find any difference in endothelial permeability between these groups. It seems that elevated blood pressure and disruption of the starling equilibrium could increase endothelial permeability (Parving and Gyntelberg 1973); however, in this study, preservation of endothelial permeability in 2K1C hypertensive group indicated that change of hemodynamic forces in hypertension does not contribute in endothelial permeability (Pedrinelli et al 1999). In agreement to our results, a recent clinical study evaluated systemic capillary permeability using TERalb (another parameter for estimation of capillary permeability) and found that systemic capillary permeability was not different between normotensive and hypertensive group (Dell'Omo et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…31 On one hand, consistent evidence does suggest that hypertensive microalbuminuria is associated with circulating markers of endothelial dysfunction, [32][33][34][35] including von Willebrand Factor, an endothelial haemostatic factor and a predictor of cardiovascular death. 36 On the other hand, however, urine albumin was dissociated from both the transcapillary 125 I-albumin escape rate, a measure of systemic capillary permeability, 28,37 and forearm vasodilatation to acetylcholine, 38 a compound that releases nitric-oxide from endothelial cells. 31 Thus, microalbuminuria may not reflect defects of specific endothelial functions such as macromolecular permeability 39 and nitric-oxide release, 31 but rather represent a non-specific response to inflammatory stimuli, in itself a cardiovascular risk factor.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…3,4 In mild, uncomplicated hypertension the main determinant of urine albumin excretion is thought to be increased haemodynamic load, 2,5,6 whereas increased glomerular vascular permeability as part of a generalised vascular dysfunction 7 is thought to be increasingly important for elevation of urine albumin excretion in moderate to severe hypertension, especially if associated with metabolic abnormalities. 8,9 Although elevated urine albumin excretion has been associated with many known cardiovascular risk factors like blood pressure (BP), 2 smoking, 10 serum homocysteine, 11 racial differences, 12 LV hypertrophy, 6 plasma glucose and serum insulin, 9 elevated urine albumin excretion has in some studies been demonstrated to be an independent predictor of cardiovascular disease and increased all-cause mortality in non-diabetic subjects as well as in patients with hypertension. 4,13,14 In hypertensive patients with LV hypertrophy on electrocardiography (ECG) we recently found that elevated urine albumin excretion assessed as increased urine albumin/creatinine ratio (UACR) and LV mass assessed by ECG were related to high BP suggesting parallel cardiac and glomerular vascular damage.…”
Section: Introductionmentioning
confidence: 99%